Microstructural and photocatalytic performance of BaCexTi1−xO3 ceramics. (January 2018) - Srikanth, K.S.; Kushwaha, H.S.; Vaish, Rahul
Abstract: In this article, the role of cerium dopant on microstructural, photocatalytic and hydrogen production performance of BaCex Ti1−x O3 (BCT) ceramics with compositions x = 0, 0.1, 0.12 and 0.15 is investigated in detail. The photocatalytic degradation experiments revealed that the synthesized catalysts had a high photocatalytic activity with cerium addition towards anionic synthetic dye methyl orange (MO) under visible light irradiation. Ce doping improves the photocatalytic hydrogen production rate via increased absorbance of visible light irradiation as the band gap shifts towards visible region with increase in x. The maximum H2 production was observed as 480 μmoleg −1 by using BaCe0.15 Ti0.85 O3 . The effect of different charge-trapping agents on photocatalytic degradation was studied to examine the role of active species and the degradation pathway.